Interpreting in multilingual, multicultural contexts - McKee, Rachel Locker, 1963-; Davis, Jeffrey Edward, 1953- (Washington, D.C. : Gallaudet University Press, 2010)
Lit. opg.; reg.
"Nineteen international interpreting authorities contribute their research and findings to Interpreting in Multilingual, Multicultural Contexts, the seventh volume in the Studies in Interpretation series. These experts probe the complex nature of interpreted interaction involving Deaf and hearing people of diverse linguistic and cultural backgrounds. They also analyze the contextualized interpreting practices and considerations that transpire from this diversity." "In three parts, this trenchant collection shows how Deaf and hearing people use language in fluctuating ways to connect with each other. The chapters in Part I.-Expanding Frontiers: ASL-English-Spanish Interpreting in the United States-consider sign language interpreting at the border between Baja California and the state; trilingual video relay service (VRS) interpreting; and constructing a valid, reliable trilingual interpreting testing instrument. Part 2-Mediating Indigenous Voices-explores how to construct roles in a Maori Deaf trilingual context; considerations for interpreting signed languages of American Indian Communities; and interpreting for indigenous Deaf clients in far north Queensland, Australia." "In the final section, Part 3-Globalizing: Interpreting in International Contexts-protocols for interpreting in multilingual international conferences are analyzed. The last chapter describes the arduousness of sign language interpreting in multilingual, international settings. It acts as a fitting conclusion to this examination of the challenges to the sociolinguistic repertoire of interpreters mediating across multiplex combinations of culture and language."--Jacket.
Expanding frontiers : ASL-English-Spanish interpreting in the United States. Sign language interpreting at the border of the two Californias / Claire Ramsey and Sergio Peña ; Trilingual Video Relay Service (VRS) interpreting in the United States / David Quinto-Pozos, Kristie Casanova de Canales, and Rafael Treviño ; Constructing a valid and reliable trilingual interpreting testing instrument / Roseann Dueñas Gonzáles, Paul Gatto, and John Bichsel -- Mediating indigenous voices. Constructing roles in a Māori deaf trilingual context / Rachel Locker McKee and Stephanie Awheto ; Signed languages of American Indian communities : considerations for interpreting work and research / Jeffrey E. Davis and Melanie McKay-Cody ; Interpreting for indigenous Australian deaf clients in Far North Queensland Australia within the legal context / Karin Fayd'herbe and Ryan Teuma -- Globalizing : interpreting in international contexts. Developing protocols for interpreting in multilingual international conferences / Ted Supalla [and others] ; Sign language interpreting in multilingual international settings / Maya de Wit.
Includes bibliographical references and index.
Keywords: Interpreters for the deaf; Multilingualism; Sign language -- Translating; Language and culture -- Translating; Deaf -- Means of communication; Hearing impaired -- Language; Indian sign language